Dynamic Changes in Land Cover and Its Effect on Urban Heat Islands - Linxue Tian; Jun Yang; Cui Jin (IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing, 2024)
Several studies have demonstrated that the urban heat island (UHI) impact is significantly influenced by changes in urban land cover (LC). In this study, we examined the dynamic change in LC in Shijiazhuang city and its impact on UHI intensity using multisource data, including landsat and LC data. The results showed that 1) the 15-year span exhibited a substantial growth in built-up area from 14.541% to 19.718%, whereas cropland and grassland dropped by 3.342% and 3.625%, respectively. 2) The mean land surface temperature (LST) in the study area increased significantly. From a point-to-plane distribution, the high-temperature zone (>32 °C) grew, and the direction of growth was consistent with urbanization. 3) The average temperature of the barren areas was the highest, followed by the built-up areas. 4) The normalized difference vegetation index and LST have a strong negative association, showing that LST rises with vegetation loss. Our research results provide a scientific basis for deeper understanding of the mechanisms underlying UHI creation, as well as for developing logical land use strategies and evaluating the effects of urbanization on local climates.